Electricity services always in the making: Informality and the work of infrastructure maintenance and repair in an African city - Baptista, I (SAGE Publications, 2018)
Access to ‘formal’ electricity networks remains a key challenge in many African urban areas. Significant attention has been paid to how access to an electricity connection should be provided, with much less attention paid to how electricity infrastructures are operated and maintained. Attention to how utilities govern the challenges inherent to ‘informality’ in the production of ‘formal’ networked infrastructure is less common, especially in African cities. Moreover, with a few notable exceptions, studies on infrastructure maintenance and repair treat ‘informality’ as a subtext to broader examinations of the uneven urban landscapes produced through infrastructure and its mediating technologies. Drawing on a socio-technical approach to electricity infrastructures, this article explores how utilities engage with ‘informality’ to produce access to ‘formal’ electricity networks through everyday processes of maintenance and repair. To this end, the article uses the empirical case of Mozambique’s national electricity company, EDM (Electricidade de Moçambique, E.P.) and its transition to an electricity network mediated by prepayment technologies in the capital city Maputo. The article argues that a socio-technical approach to infrastructures provides key insights into how utilities implicate the spatial and socio-economic dimensions of ‘informality’ in the design, delivery, and maintenance and repair of ‘formal’ electricity networks. Utilities do so through pragmatic, situated practices that sustain and continually produce and reproduce infrastructures in cities. This highlights how infrastructures are always precarious achievements and service delivery is always a process in the making. The article is based on deskwork, archival work, and fieldwork conducted by the author in Maputo since 2013.